Adopted Korean woman with symptoms of cystitis – Delayed diagnosis of tuberculosis leading to disseminated disease. Issue 1 (2017) - Mose, Maike; Isaksen, Christin; Brix, Lau; Hamilton-Dutoit, Stephen; Tarp, Britta
No abstract available